2002
DOI: 10.1046/j.1570-7458.2002.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of leaf maturation and phenolics on consumption and growth of a geometrid moth

Abstract: Phenolic compounds are commonly regarded as the main chemical defenses of deciduous woody plants against insects. To examine how indices of leaf maturation (water content, toughness, and sugar/protein ratio) modified larval consumption and growth relative to phenolics and phenolic-related leaf traits, we measured consumption and growth of fourth-instar Epirrita autumnata (Bkh.) (Lepidoptera: Geometridae) larvae on three different days on young, normal, and mature leaves, respectively, from the same mountain bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 24 publications
5
75
2
Order By: Relevance
“…Rapid developmental changes, together with high among and within tree variation in both secondary and primary compounds in mountain birch leaves, have complicated the search of induced defensive factors (Haukioja et al 1988;Kause et al 1999;Haukioja et al 2002). Condensed tannins increase with leaf maturation, whereas flavonoids and hydrolyzable tannins decrease (Salminen et al 2001(Salminen et al , 2002Riipi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid developmental changes, together with high among and within tree variation in both secondary and primary compounds in mountain birch leaves, have complicated the search of induced defensive factors (Haukioja et al 1988;Kause et al 1999;Haukioja et al 2002). Condensed tannins increase with leaf maturation, whereas flavonoids and hydrolyzable tannins decrease (Salminen et al 2001(Salminen et al , 2002Riipi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the contents of several individual HTs, flavonoids, and total HPLCphenolics similarly decreased during leaf maturation, whereas chlorogenic acid, coumaroylquinic acids, and pedunculagin derivative increased. Haukioja et al (2002) found that specific defensive leaf traits are sensitive to simultaneous variation in other leaf components and that different instars might be vulnerable and affected by different factors. Here, the contents of HTs determined from young third instar leaves negatively correlated with final pupal weight in the DIR trees, suggesting that early phases in larval development are critical for final pupal weights, although most of the weight gain is attained during the last fifth instar (see also Tammaru 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on the mechanisms of birch resistance to herbivores have focused primarily on the role of internal leaf phenolics against larvae of the autumnal moth E. autumnata (Kause et al, 1999a;Ossipov et al, 2001;Haukioja et al, 2002;Henriksson et al, 2003). In a recent study (Valkama et al, 2003), we discovered that the leaf surfaces of four Finnish birch species contain flavonoid aglycones, which are secreted by glandular trichomes.…”
Section: Introductionmentioning
confidence: 99%
“…et al , 1999a;Haukioja et al, 2002). However, several studies conducted on relationships between individual phenolic compounds and herbivory have given contrasting results Ruuhola et al, 2007).…”
Section: Discussionmentioning
confidence: 99%